If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29x + -10 + -13x = 4(4x + -3) + 2 Reorder the terms: -10 + 29x + -13x = 4(4x + -3) + 2 Combine like terms: 29x + -13x = 16x -10 + 16x = 4(4x + -3) + 2 Reorder the terms: -10 + 16x = 4(-3 + 4x) + 2 -10 + 16x = (-3 * 4 + 4x * 4) + 2 -10 + 16x = (-12 + 16x) + 2 Reorder the terms: -10 + 16x = -12 + 2 + 16x Combine like terms: -12 + 2 = -10 -10 + 16x = -10 + 16x Add '10' to each side of the equation. -10 + 10 + 16x = -10 + 10 + 16x Combine like terms: -10 + 10 = 0 0 + 16x = -10 + 10 + 16x 16x = -10 + 10 + 16x Combine like terms: -10 + 10 = 0 16x = 0 + 16x 16x = 16x Add '-16x' to each side of the equation. 16x + -16x = 16x + -16x Combine like terms: 16x + -16x = 0 0 = 16x + -16x Combine like terms: 16x + -16x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 7+44z=35z^2 | | x+250=2x | | 12.50n+35=15.00n+22.50 | | 1.25r+37=2.00r+19 | | 5a+1=a+1 | | x^2=81x | | 8(x-6)=5 | | 8(x-6)=0 | | x^2+17+20=0 | | 3x^2+35x-9.5=0 | | 25x^2-x=0 | | y^2+2y+20=0 | | -3x^2+27x=0 | | 7[9-7(8-b)]-9=9[7(9b-8)+6]-82 | | 17(3m+2)= | | 5x-7(x-8)=48 | | c=2.02w+15.83 | | 18(n+1)= | | (9x^3-4x^2-7)+(-2x^3-2x-4)=0 | | a^2+1=25 | | =5x^2-8x-4 | | =27x^2-90x+27 | | 9x^2+12x+4=12 | | (n+9)+1= | | =3x^2-x-2 | | x(-3x+7)=21 | | 5y+-3x=5 | | -x^2+4=9x+1 | | 7(x+4)= | | 9x+6=16x+8 | | 15-x=11 | | 12v^2=27 |